SELF-CONTROL DALAM HUBUNGAN BINGE WATCHING DENGAN SLEEP QUALITY PADA MAHASISWA - Zein, Abdillah Nur; Sahrani , Riana (Fakultas Psikologi Universitas Tarumanagara, 2025)
Nowadays, everyone can watch visual entertainment on a variety of electronic devices that are connected to the internet via Over the Top (OTT) service providers. With OTT services, individuals are free to watch various TV series titles without time or location constraints, indicating full control over these OTT services. Individuals with complete control can engage in a binge-watching experience. Binge watching is defined as the activity of watching at least three episodes of a TV series in one sitting. Intense binge-watching can influence people's lives, particularly their poor sleep quality. Sleep quality is defined as one’s level of satisfaction with their sleep. Thus, self-control is critical in reducing these effects. Self-control refers to an individual’s capacity to regulate their state and responses. This study aims to investigate self-control as a moderator in the association between binge watching and sleep quality in university students. Participants in this study will be (a) university students, (b) aged 18 to 25 years old, (c) with access to OTT/streaming platforms, (d) engage in binge watching at least three episodes of a TV series in one sitting, and (e) willing to complete the provided questionnaires. Based on research findings, self-control shows no moderating effect on the association between binge-watching and sleep quality.